The Influence of Intellectual Capital on the Performance of Higher Education Institutions: The Mediation Role of Performance Measurement Systems - Suryo Pratolo; Tiyas Puji Utami; Hafiez Sofyani (Jurnal Ilmiah Akuntansi, 2022)
Higher education institutions (HEIs) have a key role in developing a country by improving the quality of human resources. Thus, this study aims to empirically examine the determinants of HEI performance, i.e., intellectual capital and performance measurement systems. This study also investigates the mediating effect of the performance measurement system itself. This quantitative study used a questionnaire survey distributed to private higher education institutions (PHEIs) located in several provinces on Java Island, Indonesia. This study employed a purposive sampling technique with respondents' criteria of structural officials in the financial sector at private higher education institutions (PHEIs) on Java Island. The questionnaire responses obtained were 186 samples, and Partial Least Square was utilized to test the hypothesis. The results exhibited that the performance measurement systems mediated the relationship between intellectual capital and HEI performance. Further, this research contributes theoretically and practically, especially in implementing intellectual capital mobilized in the performance measurement system to improve the performance of HEIs.